Game development essentials : mobile game development. - Unger, Kimberly, ....-; Novak, Jeannie, 1966- ([S.l.] : Delmar Cengage Learning, 2012)
Explore a comprehensive examination of the art and technology of one of the fastest-growing segments of the game industry with GAME DEVELOPMENT ESSENTIALS: MOBILE GAME DEVELOPMENT. This ground breaking text walks readers through the overall process of designing videogames and applications for mobile and handheld hardware. Through coverage of team building, production, QA and a look at the black box of the publication process both for independent and publisher backed studios; readers learn the entire development process from initial concept to game design. Utilizing real-life examples, interviews and advice from developers already well established in the mobile industry, MOBILE GAME DEVELOPMENT serves as the 'how to' guide for readers looking to break into the mobile game development industry.